Bacterial chondronecrosis with osteomyelitis lameness in broiler chickens and its implications for welfare, meat safety, and quality: a review - Anthney, Amanda; Do, Anh Dang Trieu; Alrubaye, Adnan A. K. (Frontiers in Physiology, 2024)
The exponential increase in global population continues to present an ongoing challenge for livestock producers worldwide to consistently provide a safe, high-quality, and affordable source of protein for consumers. In the last 50 years, the poultry industry has spearheaded this effort thanks to focused genetic and genomic selection for feed-efficient, high-yielding broilers. However, such intense selection for productive traits, along with conventional industry farming practices, has also presented the industry with a myriad of serious issues that negatively impacted animal health, welfare, and productivity -such as woody breast and virulent diseases commonly associated with poultry farming.Bacterial chondronecrosis with osteomyelitis (BCO) lameness is one such issue, having rapidly become a key issue affecting the poultry industry with serious impacts on broiler welfare, meat quality, production, food safety, and economic losses since its discovery in 1972. This review focuses on hallmark clinical symptoms, diagnosis, etiology, and impact of BCO lameness on key issues facing the poultry industry.